If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(900 + -1n) = 0 (900 * 3 + -1n * 3) = 0 (2700 + -3n) = 0 Solving 2700 + -3n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2700' to each side of the equation. 2700 + -2700 + -3n = 0 + -2700 Combine like terms: 2700 + -2700 = 0 0 + -3n = 0 + -2700 -3n = 0 + -2700 Combine like terms: 0 + -2700 = -2700 -3n = -2700 Divide each side by '-3'. n = 900 Simplifying n = 900
| 27-6x=-9 | | 2x^2+12x+28=0 | | 1/10(a+1)=1/6(2-a) | | m/4=12 | | 3n-900= | | (8p+1)+3=-12 | | a+6(9a+4)=170 | | 8p+1+3=-12 | | (4(8x-2))/3x=10 | | 9x-6x+8=x-7+15 | | 5/4e+1/2=2e-1/2 | | N/4=15 | | 3a-8=16 | | 5xy-3x=0 | | x=5/8/10 | | -3/4N=33 | | -2/3y=16 | | (9x+2)(x^2+6x)= | | a+7(3a+-2)=96 | | .06a=-2.52 | | (4(8x-2))/3x | | 5/9+a=-4/9 | | x-(-5)=230 | | (-21-9b)+15= | | 60x[10s]= | | Y=80+0.6Y+30 | | 4(7x+6)=-60 | | 9v^2-10v+1= | | 24=12/x | | N+32=636 | | a+7(3a+-2)=86 | | 6x^2-35x+49= |